Ranges of B, Cd, Cr, Cu, Fe, Pb, Sr, Tl, and Zn Concentrations and Isotope Ratios in Environmental Matrices from an Urban Area - Pallavicini, Nicola; Engström, Emma; Baxter, Douglas C.; Öhlander, Björn; Ingri, Johan; Hawley, Scott; Hirst, Catherine; Rodushkina, Katerina; Rodushkin, Ilia (Journal of Spectroscopy, 2018)
Isotopic information may provide powerful insight into the elemental cycling processes which occur in natural compartments. Further implementation of isotopic techniques in natural sciences requires a better understanding of the range of elemental and isotopic compositional variability in environmental matrices. This study assesses the local-scale concentration and isotopic composition variability of nine elements: boron (B), cadmium (Cd), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), strontium (Sr), thallium (Tl), and zinc (Zn) in lysimetric waters, mushrooms, litter, needles, leaves, and lichens. Sequential extractions were also performed on soil samples from 6 depth profiles providing more detailed information on the variability of elemental concentrations and isotope ratios between the elemental pools present in soil. For most of the sample types studied the range of isotopic variability between samples spans almost the entire ranges reported in the literature for natural samples. These results represent a starting point for discussing the role of natural variability in isotopic studies (for example, as a limiting factor in the use of isotopic mixing models) and a baseline for future in-depth studies examining the controls on isotope fraction in natural systems.